ANALISIS KINERJA PENYALURAN KREDIT USAHA MIKRO DAN DAMPAKNYA TERHADAP PENINGKATAN PENDAPATAN USAHAâ€ STUDI KASUS DI KANTOR UNIT MIKRO PT BANK KALBAR CABANG PASAR MAWAR PONTIANAK (PERIODE 2013 S/D SEPTEMBER 2015) - B61108030, ZIAD YAHYA (Jurnal Ekonomi Daerah (JEDA), 2016)
This study was conducted to analyze the performance of micro-enterprise lending KUM PT Bank Kalbar Pontianak in Pasar Mawar Branch and to find out how much the provision of micro credit influences the debtor's business income levels. The purpose of this study were: 1) to analyze the performance of micro credit KUM PT Bank Kalbar Pontianak in Pasar Mawar Branch. 2) to examine and analyze the effect of micro credit KUM PT Bank Kalbar Pontianak in Pasar Mawar Branch upon the level of operating revenues. Micro credit KUM PT Bank Kalbar Pontianak in Pasar Mawar Branch was considered quite effective, with value of NPL is below 1%. Meanwhile, in the judgment of the customer, micro credit have been effective. It is based on parameters such as lending procedures, fees, the realization of the credit, interest rates, collateral, and service personnel. Parameters that has the biggest value is the service from the employee while the smallest value is the realization of the credit. Based on the test results t is known that the provision of loans has been able to increase operating income respondents. It is shown from the results of the trading operating income increased by 22.68%, a cottage industry business increased by 23.52%, business services increased by 30.51%, the restaurant business increased by 27.70%, craftsman businesses increased by 25 , 06%, and agriculture / plantation / farm increased by 22.20%. Keyword : Performance of micro credit KUM PT. Bank Kalbar